Current history (Events Pub. Co., 2009)
Current History enjoys a unique place among America's most distinguished periodicals.The oldest US publication devoted exclusively to world affairs, Current History was founded by The New York Times in 1914 to provide detailed coverage of what was then known as the Great War. As a privately owned publication, Current History has continued a long tradition of groundbreaking coverage, providing a forum for leading scholars and specialists to analyze events and trends in every region of a rapidly changing world. Current History publishes nine times per year. Each month's issue focuses on a single region or topic--including annual issues on China and East Asia, Russia and Eurasia, the Middle East, Latin America, South and Southeast Asia, Europe, and Africa.